2009
DOI: 10.1002/adfm.200900396
|View full text |Cite
|
Sign up to set email alerts
|

Phototunable Azobenzene Cholesteric Liquid Crystals with 2000 nm Range

Abstract: Phototuning of more than 2000 nm is demonstrated in an azobenzene‐based cholesteric liquid crystal (azo‐CLC) consisting of a high‐helical‐twisting‐power, axially chiral bis(azo) molecule (QL76). Phototuning range and rate are compared as a function of chiral dopant concentration, light intensity, and thickness. CLCs composed of QL76 maintain the CLC phase regardless of intensity or duration of exposure. The time necessary for the complete restoration of the original spectral properties (position, bandwidth, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 49 publications
0
101
0
Order By: Relevance
“…In the past decade, a number of light responsive chiral dopants which can change their HTP either upon isomerization or helical inversion have been used to tune the position of a cholesteric reflection notch over a wide range. [116][117][118] A light responsive system which can change its reflection bandwidth based on the intensities of light would be very attractive. First steps for such a responsive system in the visible and infrared regions have been taken by White et al using a chiral azobenzene photoisomer doped in a Ch-LC cell.…”
Section: Outlook and Future Challengesmentioning
confidence: 99%
“…In the past decade, a number of light responsive chiral dopants which can change their HTP either upon isomerization or helical inversion have been used to tune the position of a cholesteric reflection notch over a wide range. [116][117][118] A light responsive system which can change its reflection bandwidth based on the intensities of light would be very attractive. First steps for such a responsive system in the visible and infrared regions have been taken by White et al using a chiral azobenzene photoisomer doped in a Ch-LC cell.…”
Section: Outlook and Future Challengesmentioning
confidence: 99%
“…In CLC, the birefringent molecules self-assemble with the director (crystalline) axis arranged in a spiral, with a pitch on the order of the optical wavelength stretching from the UV to the infrared regime, as seen in Figure 12. As a result, CLC's possess not only the advantageous features of liquid crystals such as fabrication ease and low cost, and a very wide spectral dynamic range of operation [68,69], but also the 1-D photonic crystals' unique ability to enhance the nonlinear ultrafast all-optical responses of the CLC constituent molecules [mostly due to the nematic constituent], in addition to the dispersion effect at the photonic band-edges. A typical magnitude of the non-resonant nonlinear index coefficient n 2 is in the order of 10 −14 -10 −13 cm 2 /W, but owing to the photonic crystal band-edge enhancement, the magnitude of the effective n 2 can be as large as 10 −12 -10 −11 cm 2 /W.…”
Section: Ultrafast Pulse Modulations Based On Cholesteric Liquid Crysmentioning
confidence: 99%
“…[14,26] Recently, we reported the synthesis of a planar chiral azobenzene consisting of a di-A C H T U N G T R E N N U N G oxynaphthalene moiety that was cyclically bonded at the meta positions of azobenzene by bismethylene spacers, which was successfully employed as a chiroptical switch in commercially available liquid crystals, giving rise to phototunable reflection colors.…”
Section: Introductionmentioning
confidence: 99%
“…[1,12] Moreover, the intriguing science behind photoinduced chirality is also attracting the attention of many researchers owing to its the possible applications in chiral sensors [13] and switches. [14] Following studies by le Bel [15] and Van't Hoff [16] that demonstrated the potential usefulness of l-or r-circular polarized light (l-or r-CPL), several attempts have been made to achieve enantiomeric enrichment using CPL. Among the various photocontrolled chiral induction processes, reversible enantio-differentiating photoisomerization is known to take place in a number of compounds for which photoresolution and photoracemization occur with CPL and normal light, respectively.…”
Section: Introductionmentioning
confidence: 99%